(untitled) (Economic and Political Thought, 2023)
Undoubtedly, already during Barack Obama’s presidency, Asia, including China, became a key point of the US foreign policy, and the so-called “Pivot to Asia” was a great proof for that. However, while Obama still seemed to treat China as a strategic partner, not seeing it as an existential threat, Trump decisively changed this approach and gave a new direction to the American strategy towards China – from then on, China officially became a “strategic rival” and the goal was to slow down its growth in the key areas that threatened US security and its global hegemony. The author puts forward the thesis that Joe Biden mostly continues Trump’s decisive course towards China. Analyzing and comparing official documents of the US government (the American Defence Strategy of 2020 and 2022 and two key documents/ speeches presenting the US approach to China during the administrations of Donald Trump and Joe Biden), the author comes to the conclusion that the current president not only continues the course of his predecessor, but also strengthens it in a few selected areas, such as high technologies and rare earths. The author also attempts to explain the reasons for the following continuation in the US approach to China.